Control of ovine brucellosis in a high performance sheep flock using multiple serological tests - SINGH, S V; GUPTA, V K; SINGH, N (The Indian Journal of Animal Sciences, 2013)
A flock of Muzaffamagri sheep was under surveillance for incidence of reproductive losses, diagnosis and control of Brucella infection using Standard tube agglutination test (SAT) and multiple serological tests (SAT, CFT, plate-ELISA and dot-ELISA). Dot-ELISA showed better sensitivity than the SAT, eFT and plate-ELISA. At least 10.6% lambs were lost due to abortions (9.8%) and stillbirths (O.S%) from 1991 to 1995. Screening of the flock with the qualitative dot-ELISA and further quantification of positive reactors by other tests led to detection of 18.0%, 3.6% and 4.2% seropositive cases in January, 1993, September, 1993 and January, 1994 respectively. Removal of positive reactors after multiple tests screening apparently led to marked reduction in reproductive losses and prevalence of brucellosis in the flock.